Resistance and radical democracy: freedom, power and institutions. Issue 4 (19th May 2018) - Hamilton, Lawrence
ABSTRACT: In this article, I argue that resistance and radical democracy can be used to the good of representative democracy. I submit that resistance is about the popular power – the freedom as power – to create better institutions. I argue that the conflict and resistance that is at the core of radical democracy enables freedom and democracy and resists domination best if it is institutionalized. This counterintuitive claim is substantiated by an argument for freedom as power through representation and how the power to resist is linked to at least four domains of freedom. This builds on the work of Machiavelli, Marx and Foucault, amongst others, and insights drawn from resistance struggles across the globe. I end by proposing institutional changes to representative democracy that, I suggest, would allow us to conceive of democracy as both a form of government and a constantly destabilizing transgressive practice.